Dead medics' society - Albany, Mike (Tfm Publishing, 2005)
David Gray is a disillusioned surgeon approaching retirement. One night, on the way home from an emergency aneurysm repair, he has a car crash and meets the spirit of the patient he's just operated on -- a man called Alf Angel. Alf, a simple and straightforward character, becomes Gray's guardian and travelling companion on a fantastic journey through time. They visit scenes from Gray's formative years as a young medic, before moving further back in time to learn something of the early trials and tribulations of scientific surgery. Through it all, Gray earnestly seeks the worth of his calling as a doctor and surgeon and ultimately, the nature and meaning of life itself. This is a short novella told in a tongue-in-cheek style using a mixture of amusing whimsy and, at times, profound insight into the minds of men who wield scalpels for a living. Although this short tale is clearly fiction, the historical figures and operations depicted are real, though the characterisation is down to poetic license. Read it and wonder.